Immunomodulatory Effects of the Aromatic Geranyl Derivative Filifolinone Tested by the Induction of Cytokine Expression - Torres-Gaona, M; Imarai-Bahamonde, C; Modak-Canobra, B; Valenzuela-Montenegro, B (2013)
Sin Editorial Disponible